ACADEMIC LEADERSHIP STYLES AND SUPPORT FOR STRATEGIC PLANNING AT HIGHER EDUCATION INSTITUTIONS IN CAPPADOCIA REGION, TURKEY - (:unkn) unknown (My University, 2015)
Öğretim üyelerinin desteği ve etkin akademik liderlik stratejik planların başarıyla uygulanmasında önemli faktörler olsa da bu konularla ilişkili çalışmaların az sayıda olduğu görülmektedir. Bu çalışmada Kapadokya bölgesinde bulunan dokuz üniversitede gerçekleştirilen keşfedici bir araştırma projesinin sonuçları sunulmaktadır. Dört yıllık lisans eğitimi veren fakültelerde görevli öğretim üyelerinden elde edilen 233 anket analiz edilmiştir. Grup farklılıkları ANOVA ve t-testleri, öğretim üyelerinin stratejik planlamaya destekleri ve algılanan liderlik stilleri arasındaki ilişkiler ise çoklu regresyon ile analiz edilmiştir. Bulgular akademik unvan, cinsiyet, disipliner farklılıklar ve yönetici rolü değişkenleri açısından anlamlı farklılıklar olduğunu göstermiştir. Çoklu regresyon analizi girişimci liderlik stilinin stratejik planlama faaliyetlerine destek konusunda anlamlı pozitif etkiye sahip olduğunu göstermiştir.

Although faculty support and effective academic leadership are crucial factors in successful implementation of strategic plans, there seems to be few studies which investigate the faculty support for strategic planning and the role of academic leadership styles in fostering support for strategic planning. In this paper we present the results of an exploratory research project which was conducted at nine universities around Cappadocia Region in Turkey. We analyzed data acquired from 233 questionnaires which were gathered from academics who are employed at four year faculties. We examined group differences with ANOVA and t-tests, and we explored the relationship between support for strategic planning among faculty and the role of perceived academic leadership styles with multiple regression analysis. The findings show that academic titles, gender, disciplinary differences, and administrative roles have significant effects on support for strategic planning and perceived leadership styles. Multiple regression analysis revealed that entrepreneurial leadership style has significant positive effect in fostering support for strategic planning activities.
TÜRKİYE KAPADOKYA BÖLGESİNDEKİ YÜKSEKÖĞRETİM KURUMLARINDA AKADEMİK LİDERLİK STİLLERİ VE STRATEJİK PLANLAMAYA DESTEK
Keywords: İktisat; İşletme